Efektivitas Kebijakan Pemerintah Dalam Pemindahan Pedagang Kaki Lima (PKL) Di Jalan Pase Kota Lhokseumawe Studi Di Kecamatan Banda Sakti Kota Lhokseumawe - Nurmasyahyati, Nurmasyahyati; Aruni, Fidhia; Muhaddis, Muhaddis; Farida, Ratna; Fauzan, Fauzan (Universitas Pahlawan Tuanku Tambusai, 2024)
Banda Sakti District, which is the capital of Lhokseumawe, certainly requires the development of city infrastructure that is orderly, neat, orderly and has comfortable open spaces, so that it is not disturbed by street vendors selling in front of shops, on the side of the road, on the sidewalks on Jalan Pase. The aim of this research is to describe the effectiveness of government policy in removing street vendors. The method used in this research is descriptive qualitative research through interviews, observation and documentation, data analysis techniques are carried out through data collection, data reduction, data presentation and data verification. This research used 9 informants who were determined purposively. The results of the research found that on Jalan Pase there were 38 out of 270 street vendors selling on the side of the road, in front of shops, on sidewalks, in front of offices and schools and were not willing to move to the location (relocation) that had been provided by the Lhokseumawe City Government due to relocation (place new) does not match the condition. The conclusion is that the government policy of Lhokseumawe Mayor Regulation Number 06 of 2010 concerning the relocation of controlling street vendors has been implemented through an individual approach by providing warnings, but the government's objectives regarding the relocation of street vendors have not been realized effectively, because the street vendors have not been successfully moved to the new relocation .